If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -21 = 5x + -3y + -12 Reorder the terms: -21 + 2x = 5x + -3y + -12 Reorder the terms: -21 + 2x = -12 + 5x + -3y Solving -21 + 2x = -12 + 5x + -3y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -21 + 2x + -5x = -12 + 5x + -5x + -3y Combine like terms: 2x + -5x = -3x -21 + -3x = -12 + 5x + -5x + -3y Combine like terms: 5x + -5x = 0 -21 + -3x = -12 + 0 + -3y -21 + -3x = -12 + -3y Add '21' to each side of the equation. -21 + 21 + -3x = -12 + 21 + -3y Combine like terms: -21 + 21 = 0 0 + -3x = -12 + 21 + -3y -3x = -12 + 21 + -3y Combine like terms: -12 + 21 = 9 -3x = 9 + -3y Divide each side by '-3'. x = -3 + y Simplifying x = -3 + y
| (2x-7)+(3x+4)=0 | | 10x^4=0.001 | | (7/4)(-5) | | 15p+p+-19p+20p+-14p-16=-2 | | 8r+2r-2r-3r-3r=20 | | -5n-(-14n)+-11n+-4n=18 | | 2(x-4)-3(5x-1)=8 | | 7j+6j-12j=17 | | -13h+8h+10h=-20 | | -5x+4x=-20 | | (1-2a)x^2-2ax-1=0 | | 4x^2-29+5x+1=0 | | 9(6x+2)whenx=9 | | (8+i)(7+5i)=0 | | 2*m*n*8= | | 3x+12-5x+10=2x-5x+5 | | q^2-11q+30=0 | | -10x+30=-3x+100 | | 4/x-2=43 | | x^2-8x-15=3x-3 | | x^2+10x+3=7x+1 | | 9x-2=4x+x+4 | | 5/2x=43/4 | | -3x+5=21x | | -122=-6(1-4n)+4 | | 3y-(-1)=4 | | -x-1=3x-2 | | p/4=-1and1/6 | | Y+2x-12=180 | | 1/2(4a-16)=6 | | 3x^2-16x-60=0 | | p4=-1-1/6 |